Pelvic Exam Laws in the United States: A Systematic Review. Issue 4 (December 2022) - Plantak, Mihael; Alter, Scott M.; Clayton, Lisa M.; Hughes, Patrick G.; Shih, Richard D.; Mendiola, Monica; Solano, Joshua J.
Abstract: Laws regulating patient care are an essential component of protecting patients and doctors alike. No studies have previously examined what laws exist regarding pelvic examinations in the United States (US). This study systematically reviews and compares regulation and legislation of pelvic examinations in the U.S. and provides a comprehensive resource to educate clinicians, patients, and lawmakers. Each of the fifty States in the U.S. was included. The primary outcome was existence of any pelvic or rectal exam laws. Data was obtained for the type of examination defined within the law, exceptions to the law, to whom the law applied to, the type of consent required, and to whom the consent applied to. Laws were identified from each of the individual state legislative websites. All sections of each law pertaining to pelvic examination were reviewed and organized by state. Descriptive statistics were performed for each of the variables, including frequencies of each amongst the fifty states. State regulation for pelvic examinations varied from no law or regulation to laws pertaining to pelvic, rectal, prostate, and breast examination performed in any context. As of November 22, 2022, there are twenty states (40%) with pelvic examination laws applying to anesthetized or unconscious patients. Thirteen additional states (26%) have proposed pelvic exam laws. Seventeen states (34%) do not have any laws regarding pelvic examinations. Regulation of pelvic examinations has become an increasingly important issue over the past few years in response to growing concerns of patient autonomy and the ethical issues raised by such sensitive examinations. While pelvic examination laws that balance protection for patient autonomy and the needs of caregivers and educators exist in much of the U.S., more work needs to continue in consultation with physicians and health care providers to ensure that all states have reasonable laws protecting the autonomy of patients while also maintaining quality of care.